2015
DOI: 10.18203/2320-6012.ijrms20151161
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption among adult males in urban area of Thanlyin Township, Yangon Region, Myanmar

Abstract: Alcohol consumption is a worldwide problem and frequently related to health, behavioural and socioeconomic problems. 1-4 The occurrence of these alcohol related problems is higher in males than in females of the same age group. 5,6 Almost 6% of total global deaths (7.6% for males and 4% for females), or 3.3 million deaths were related to alcohol consumption in 2012. 7 Besides, alcohol consumption is the leading cause of deaths among males between the ages of 15 and 59 years, or among people aged 15-49 years. 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 9 publications
1
6
1
Order By: Relevance
“…Studies in China and other countries also highlighted alcohol consumption among MSM and general population but using different screening tools. Additionally, previous studies have documented the prevalence of alcohol consumption at different time periods (Liu et al, 2016;Lu et al, 2019). In present study, nearly 70% of MSM had consumed alcohol within the past 3 months and 36.2% of Apwint (open type), 35.3% of Apone (hidden type) and 62.8% of Thange (sexual partners of MSM) had experience of binge drinking.…”
Section: Discussion and Recommendationsupporting
confidence: 47%
See 2 more Smart Citations
“…Studies in China and other countries also highlighted alcohol consumption among MSM and general population but using different screening tools. Additionally, previous studies have documented the prevalence of alcohol consumption at different time periods (Liu et al, 2016;Lu et al, 2019). In present study, nearly 70% of MSM had consumed alcohol within the past 3 months and 36.2% of Apwint (open type), 35.3% of Apone (hidden type) and 62.8% of Thange (sexual partners of MSM) had experience of binge drinking.…”
Section: Discussion and Recommendationsupporting
confidence: 47%
“…In Peru, 45% of MSM had an alcohol use disorder and over 90% were hazardous drinkers (Herrera et al, 2016). Another study in China among a general adult population aged 18 to 34 years also identified the prevalence of alcohol consumption as about 45% (Lu et al, 2019). Similarly, another study in US among MSM documented that nearly 14% and 25% were monthly and weekly binge drinkers (Santos et al, 2018).…”
Section: Discussion and Recommendationmentioning
confidence: 98%
See 1 more Smart Citation
“…By considering the estimated proportion of MSM who are current drinkers as 20% ( Oo et al , 2015 ), to achieve a 95% confidence level and an error of 5%, the minimum required sample size becomes 246 ( Wayne, 1995 ).…”
Section: Methodsmentioning
confidence: 99%
“…A number of proposed factors affect the magnitude and pattern of alcohol use and predisposition to the risk of alcohol use disorders. Male sex,[212223] young age,[21] older age,[24] no education or primary education,[222425] lower socioeconomic status,[25] mental disorder,[26] medicinal benefits,[27] smoking,[2829] betel nut chewing,[29] having a spouse who drinks alcohol,[25] manual laborer status,[26] and living in urban areas[23] have been identified in other studies as factors associated with alcohol use.…”
Section: Introductionmentioning
confidence: 99%